2018
DOI: 10.1186/s13075-018-1529-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired lymph node stromal cell function during the earliest phases of rheumatoid arthritis

Abstract: BackgroundSystemic autoimmunity can be present years before clinical onset of rheumatoid arthritis (RA). Adaptive immunity is initiated in lymphoid tissue where lymph node stromal cells (LNSCs) regulate immune responses through their intimate connection with leucocytes. We postulate that malfunctioning of LNSCs creates a microenvironment in which normal immune responses are not properly controlled, possibly leading to autoimmune disease. In this study we established an experimental model for studying the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…The above results indicate that TLR9 inhibits peritoneal B cell recruitment via suppression of CXCL13 production; however, how TLR9 regulates peritoneal CXCL13 levels is unclear. CXCL13 is expressed in multiple cell types other than B cells (32), including DCs (33), macrophages (34), and FRCs in FALCs (9) and lymph nodes (35). We first tested to determine whether TLR9 regulated CXCL13 production from cells in the peritoneal cavity or cells from FALCs in mesenteric adipose tissues.…”
Section: Tlr9 Signaling In Fibroblastic Reticular Cells Regulates Permentioning
confidence: 99%
“…The above results indicate that TLR9 inhibits peritoneal B cell recruitment via suppression of CXCL13 production; however, how TLR9 regulates peritoneal CXCL13 levels is unclear. CXCL13 is expressed in multiple cell types other than B cells (32), including DCs (33), macrophages (34), and FRCs in FALCs (9) and lymph nodes (35). We first tested to determine whether TLR9 regulated CXCL13 production from cells in the peritoneal cavity or cells from FALCs in mesenteric adipose tissues.…”
Section: Tlr9 Signaling In Fibroblastic Reticular Cells Regulates Permentioning
confidence: 99%
“…Similar to mice [28,30], inflammation can trigger phenotypic and transcriptional changes in human LNSCs [31], and lipopolysaccharide upregulates HLA-DR and PD-L1 in human FRCs [32]. PD-L1 is also upregulated by type I IFN during inflammation [33], and it is actually one of the mechanisms used by LNSCs (at least LECs) to control autoreactive T cells in mice [13].…”
Section: In S P T P R N G a D 2 G 6 P C 2 T Y R M L A N A T N F A Ipmentioning
confidence: 99%
“…Of these, CCL19 was an overexpressed chemokine in patients with RA. Various studies have indicated that CCL19 serves a chemotactic role in B cells, dendritic cells and naïve T cells via binding to the C-C motif chemokine receptor (CCR)7 (36)(37)(38). CCR7 is an important antigen molecule expressed on the surface of Treg cells and CCL19 may specifically bind to the receptor CCR7, which in turn exerts chemotactic activity on Treg cells (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%